If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -7(k + -6) = 31 + -8k Reorder the terms: -6 + -7(-6 + k) = 31 + -8k -6 + (-6 * -7 + k * -7) = 31 + -8k -6 + (42 + -7k) = 31 + -8k Combine like terms: -6 + 42 = 36 36 + -7k = 31 + -8k Solving 36 + -7k = 31 + -8k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '8k' to each side of the equation. 36 + -7k + 8k = 31 + -8k + 8k Combine like terms: -7k + 8k = 1k 36 + 1k = 31 + -8k + 8k Combine like terms: -8k + 8k = 0 36 + 1k = 31 + 0 36 + 1k = 31 Add '-36' to each side of the equation. 36 + -36 + 1k = 31 + -36 Combine like terms: 36 + -36 = 0 0 + 1k = 31 + -36 1k = 31 + -36 Combine like terms: 31 + -36 = -5 1k = -5 Divide each side by '1'. k = -5 Simplifying k = -5
| 4(3-2x)+4x=-4 | | 3(5x-6) | | 4y-4=y-16 | | 3t+1= | | C-7.88=9.25 | | -1+5(2n-2)=31+3n | | 3(2a+3)-4(3a-b)=15 | | 6(4x–3)–10x=14x-15 | | -158-7x=4x+51 | | 4(6n+9)-10= | | w2+36=12w | | 8(y-20=4Y | | 7+m=(m-3)+10 | | 2(1+7p)=8p-40 | | -12=4(u-2) | | t^2+1= | | 12x-4-2x=6 | | 3(x+1)-7=2-5(x-2) | | -3(k+4)=-36 | | 4n-9=2n-1 | | 3+m=7-m | | 3t+1=0 | | -3x+12-4x=-5x+16 | | 16+x=35 | | 4.9X^2+21X-300=0 | | -12=-7(u-2) | | 12w+4(6-w)=5x+17 | | 7x-2y=2x+9y | | -8x-28=-(6-3x) | | -85+5x+x=71 | | 12x-5y=-40 | | -3x+12-4x=5x+16 |